2022
DOI: 10.1007/s13346-022-01189-4
|View full text |Cite
|
Sign up to set email alerts
|

Modelling acute myeloid leukemia (AML): What’s new? A transition from the classical to the modern

Abstract: Acute myeloid leukemia (AML) is a heterogeneous malignancy affecting myeloid cells in the bone marrow (BM) but can spread giving rise to impaired hematopoiesis. AML incidence increases with age and is associated with poor prognostic outcomes. There has been a disconnect between the success of novel drug compounds observed in preclinical studies of hematological malignancy and less than exceptional therapeutic responses in clinical trials. This review aims to provide a state-of-the-art overview on the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 316 publications
0
5
0
Order By: Relevance
“…While we present ex vivo screening protocols that use the CellTiter-Glo assay or flow cytometry as a read-out, alternative approaches to ex vivo drug sensitivity screening have been established and previously reported, including three-dimensional cell culture models [ 39 43 ] and protocols with image-based read-outs [ 19 , 44 46 ]. Continuous development of the screening protocols, including the consideration of microenvironmental effects on drug sensitivity, is expected to expand their applicability, both when it comes to disease indications and to drug classes that can be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…While we present ex vivo screening protocols that use the CellTiter-Glo assay or flow cytometry as a read-out, alternative approaches to ex vivo drug sensitivity screening have been established and previously reported, including three-dimensional cell culture models [ 39 43 ] and protocols with image-based read-outs [ 19 , 44 46 ]. Continuous development of the screening protocols, including the consideration of microenvironmental effects on drug sensitivity, is expected to expand their applicability, both when it comes to disease indications and to drug classes that can be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…AML represents a heterogeneous group of hematological malignancies characterized by the abnormal proliferation of undifferentiated myeloid progenitors [9]. Various studies have reported aberrant expression of key pluripotency transcription factors (OCT4, NANOG, and SOX2) in different types of solid and hematological tumors [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complexity of AML, it is impossible to identify a single cell line to establish a universal disease model. Studies conducted in non-human animal models may not provide accurate results because of differences in AML progression across species [ 7 ]. While studies using primary samples from patients may be more similar to clinical outcomes in patients, they can be diverse due to the varied genotypes of each patient.…”
Section: Aml Cell Lines and Typesmentioning
confidence: 99%
“…On the other hand, studies using established cell lines are more cost-effective and reproducible but do not account for the variability of clinical features in patients. Therefore, combining studies using established cell lines with those using primary samples can provide more accurate results [ 7 ].…”
Section: Aml Cell Lines and Typesmentioning
confidence: 99%